THE CHALLENGES OF LEARNING ENGLISH AS A FOREIGN LANGUAGE AMONG UNDERGRADUATE STUDENTS - Alpino Susanto; A Malik A Malik; Mitrayati Mitrayati (Politeknik Negeri Bengkalis, 2020)
As one of the foreign languages in Indonesia, English must be learned from junior high school to undergraduate level. As a foreign language, challenges arise both in terms of the teacher as the one who give instruction or students as objects as well as subject learners. Various responses can be found in class related to these problems, especially in the attitude of students during the learning process, student learning outcomes, and participation in carrying out group activities. This study aims to explore the obstacles faced by students in learning English and its causal factors in the environment of Karimun University. This study uses a qualitative approach with a questionnaire, observation, and video recording instrument. Analysis of research data is done in three ways, namely, data reduction, data presentation, and drawing conclusions and verification. The results showed that the research subjects had various learning difficulties in English. This happens due to the different levels of English mastery between individuals.